Answer:
Dude I dont understand it I would leave if i knew how
Step-by-step explanation:
Answer:
Step-by-step explanation:
½(x-2) = 8 + 5x
Multiply both sides by 2
2⋅½(x-2) = 2(8 + 5x)
1(x-2) = 2(8 + 5x)
Apply the distributive rule
x - 2 = 16 + 10x
Subtract x from both sides
-2 = 16 + 9x
Subtract 16 from both sides
-18 = 9x
Divide both sides by the coefficient of x
-18 ÷ 9 = 9x ÷ 9
-2 = x
Answer:
AC and AE
Step-by-step explanation:
Those are the only secants in the image shown.
Answer:
−18b+6
Step-by-step explanation:
6(−3b+1)
Use the distributive property to multiply 6 by −3b+1.
−18b+6